When Ignorance is Bliss - Information Asymmetries Enhance Prosocial Behavior in Dictator Games - Evguenia Winschel; Philipp Zahn (Center for Economic Studies and ifo Institute (CESifo), 2014)
In most laboratory experiments concerning prosocial behavior subjects are fully informed how their decision influences the payoff of other players. Outside the laboratory, however, individuals typically have to decide without such detailed knowledge. To assess the effect of information asymmetries on prosocial behavior, we conduct a laboratory experiment with a simple non-strategic interaction. A dictator has only limited knowledge about the benefits his prosocial action generates for a recipient. We observe subjects with heterogenous social preferences. While under symmetric information only individuals with the same type of preferences transfer, under asymmetric information different types transfer at the same time. As a consequence and the main finding of our experiment, uninformed dictators behave more prosocially than informed dictators.
Keywords: D82; C91; 330; asymmetric information; prosocial behavior; efficiency concern; inequality aversion; dictator game